Identification of national hrm policy and job market demand: critical review of scientific publication - Dadang, A. M.; Asmadianto, Asmadianto; Rahayu, Sukowati Mudji (International research journal of management, IT and social sciences, 2021)
This review study obtains much literature through a systemic search of data and information that covers the two variables above. The preparation and planning of human resources is a process that has been carried out systematically to improve human resources as the main asset worthy of being unemployable. On average, we find that this HR management is urgent to ensure the suitability between human resources and work, both in terms of quantity and quality that users are interested in, the study says. The study concludes that the preparation and Planning of Human Resources is a Process.